LINEARITY OF $n$-ARY ASSOCIATIVE ALGEBRAS - Harutyunyan, David N. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In this paper n-ary regular division associative algebras are discussed.  It is shown that every operation in n-ary regular division associative algebra will be endo-linearly represented over the same binary group. Schauffler like theorem will be proved for those algebras.
Keywords: regular division groupoids; n-ary groupoids; quasiendomorphisms; Schauffler theorem